Message of Social Critism in Film “Sejuta Sayang Untuknya” - Safika Wulandari; kusmarwanti - (Cinematology: Journal Anthology of Film and Television Studies, 2022)
The film "Sejuta Sayang Untuknya" is interesting to study because this film displays signs that imply messages. This study aims to describe the construction of the meanings of symbols of social criticism messages in the film Sejuta Sayang Untuknya. This study uses a qualitative method, with a descriptive analysis approach through semiotic techniques. The researcher uses Charles Sanders Pierce's semiotic analysis model. The researcher chose cut scenes in the film Sejuta Sayang Untuknya which has a social criticism message meaning by using triangle meaning analysis. After knowing the research discussion through Charles Sander Pierce's semiotic analysis in the film Sejuta Sayang Untuknya, it can be concluded that the message of social criticism in the film Sejuta Sayang Untuknya is symbolized through character dialogues that contain elements of social criticism messages, including: messages of criticism against the government , education, law, the corrupt, and the poor. The results of this study can be used as a reference for research on film and television semiotics as well as a guide for film makers in using the symbols of meaning to be placed in a scene.Abstract